Angiography for Management of Perioperative Myocardial Ischemia: Does it Have Any Role?. Issue 5 (September 2014) - Narayan, Pradeep; Bandyopadhyay, Manujesh; Khan, Mohammed Wasim; Sarkar, Kunal
Objective: Perioperative myocardial ischemia (PMI) is a relatively rare but potentially fatal complication after coronary artery bypass grafting and is due to graft-related problems in a significant proportion of cases. The usual indicators of MI in the postoperative setting are unreliable and therefore have uncertain diagnostic value. Angiography, the criterion standard for preoperative angina, remains underused for evaluation of PMI. The aim of this study was to evaluate the role of angiography in the management of PMI. Methods: Between January 2011 and September 2012, a total of 2312 isolated primary consecutive coronary artery bypass graft surgeries were performed, of which 2057 (89%) were carried out on the beating heart. Twenty-six (1.12%) of these patients needed perioperative angiography. The patients needing angiography were selected on the basis of a number of clinical, biochemical, and other diagnostic parameters Results: Twenty-six patients with PMI required angiography, of which 18 (69 %) were found to have graft-related issues. The mean (SD) time between operation and angiography was 24.58 (6.71) hours. Of the 18 patients, 17 (94.44%) required surgical intervention and 1 patient was treated with angioplasty. There were 2 deaths (11.1%) in the group undergoing intervention. Angiographic findings included occluded vein graft (n = 7), narrowing of the left internal mammary artery (n = 3), and kinking or stretching of grafts (n = 8). Conclusions: Angiography is useful in diagnosing graft-related problems in the perioperative period. In presence of signs of graft compromise, we suggest that having a low threshold for angiographic graft evaluation may be beneficial in a carefully selected subset of patients after coronary artery bypass.